Correction: Can big data reduce urban environmental pollution? Evidence from China's digital technology experimental zone. - Jiahao Zhang; Fusheng Liang; Peng Gao (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0288429.].